PENGARUH KEPEMIMPINAN, KEMAMPUAN INDIVIDU DAN PENGAWASAN TERHADAP KINERJA KARYAWAN KOPERASI CU CINTA KASIH TIGAPANAH - Tinambunan, Anitha Paulina; Jawak, Putri Sari Endang (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This study aims to examine the influence of leadership, individual capability, and supervision on employee performance at CU Cinta Kasih Tigapanah Cooperative. The research population consists of 37 employees, with a saturated sampling technique applied. Data collection was conducted through questionnaires and analyzed using SmartPLS version 4.0. The results indicate that leadership has a positive and significant effect on employee performance, with a T-statistic value of 4.082 (greater than 1.96) and a P-value of 0.000 (less than 0.05). Similarly, individual capability also significantly affects employee performance, with a T-statistic value of 2.073 and a P-value of 0.019. Moreover, supervision positively and significantly influences employee performance, with a T-statistic value of 2.014 and a P-value of 0.022. These findings demonstrate that leadership, individual capability, and supervision collectively have a positive and significant impact on employee performance at CU Cinta Kasih Tigapanah.